(untitled) (Research, Society and Development, 2020)
The use of natural starter culture in the manufacture of artisanal Minas cheeses is required by the government legislation in Brazil. However, there are no scientific support on role of the natural starter culture in these cheeses. The aim of this work was to compare artisanal Minas cheeses produced with and without natural starter culture to verify the influence on the physico-chemical and microbiological characteristics during the ripening process. The use of natural starter culture did not have a significant effect on the physico-chemical (dry matter, humidity, fat, pH, chlorides, water activity, ash, total protein, depth and extent of proteolysis) and microbiological (Escherichia coli, coliforms and Staphylococcus aureus) properties of the cheeses. The significant changes that occurred in the cheeses were mainly because of the ripening time. According to obtained results, natural starter has shown to be innocuous to traditional Minas Serro cheese. The present study is pioneering in the scientific literature and opens new horizons for the understanding of the requirement to use natural starter culture.